2007
DOI: 10.1007/s00234-007-0333-y
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured, dissecting posterior inferior cerebellar artery aneurysms: endovascular treatment without parent vessel occlusion

Abstract: Coiling of ruptured, isolated dissecting aneurysms of the PICA without parent vessel occlusion is feasible, relatively safe and effective in preventing early/medium-term rebleeding. A strict angiographic follow-up program is, however, necessary to detect recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…The natural history of distal segment dissecting PICA aneurysms is likely different from the more common saccular aneurysms, which frequently arise at the vertebral artery-PICA junction. 11 One author reported a high rebleeding risk (24%) in the acute phase of the posterior circulation dissections, with an associated high mortality rate. 18 We had 1 patient (17%) with rebleeding in the acute phase who was treated when the second hemorrhage occurred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The natural history of distal segment dissecting PICA aneurysms is likely different from the more common saccular aneurysms, which frequently arise at the vertebral artery-PICA junction. 11 One author reported a high rebleeding risk (24%) in the acute phase of the posterior circulation dissections, with an associated high mortality rate. 18 We had 1 patient (17%) with rebleeding in the acute phase who was treated when the second hemorrhage occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Successful endovascular embolization of dissecting PICA aneurysms has been reported 8,24 and is considered relatively safe and reliable. Cellerini et al 11 reported successful endovascular treatment of ruptured dissecting PICA aneurysms without parent vessel occlusion in 6 patients. In their series, despite complete embolization of the aneurysms after the procedure, they had 3 early recurrences (27%), which represents a relatively high rate of early recurrence given the small series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,16 Both microsurgical and endovascular treatment options exist, with acceptable rates of aneurysm occlusion; however, longterm outcome data are lacking for SAH patients with ruptured PICA aneurysms. [2][3][4][5][6]13,16 In this study, we aim to better define the clinical nuances, complications, and longterm outcomes of ruptured PICA aneurysms in patients who were treated as part of the Bar row Ruptured Aneurysm Trial (BRAT) and compare the clinical characteristics of those with ruptured PICA an eurysms versus those with all other types of ruptured in tracranial aneurysms. 12 We hypothesize that patients with ruptured PICA aneurysms fare worse than those with rup tured aneurysms in other locations and that the high rate of lower cranial nerve dysfunction may help to explain this worse outcome.…”
mentioning
confidence: 99%